THE RELATIONSHIP BETWEEN NURSE EMPOWERMENT AND QUALITY OF NURSING WORK LIFE IN HOSPITAL - Rizeki Dwi Fibriansari (UPT Penerbitan Universitas Jember, 2017)
Background: Nursing human resources are a very important asset and component of a hospital service, contributing 55-65% to the hospital image out of the total number of employees. The utilization of human resources is essentially a form of employee empowerment in a hospital. The empowerment of hospital nurses will give a positive impact to nurse satisfaction, customer satisfaction, and organization, but it is still common to find hospitals that still lack in empowering their employees. This research is aimed at determine the relationship between nurse empowerment and Quality Of Nursing Work Life (QNWL). Methods: This study used a cross-sectional approach. The population is nurses who have the status as civil servants at a Dr Haryoto Hospital Lumajang, and by using a multi-stage sampling, 134 respondents were obtained. Data were collected by the questioner and were analyzed by using Spearman’s Rho correlation with a significance level of 0.01. Results: The result showed variable of structural empowerment, the highest category is opportunity with 46%, in the psychological empowerment is confidance with 63%, while at the QNWL, work context received 54%. Empowerment was significantly related to QNWL (p=0.000, r=0.326). Structural empowerment was related with QNWL (r=0.286) and psychological empowerment too (r=0.213). So empowerment was able to increase QNWL by 32.6%. Conclusions: Empowerment had a direct influence on QNWL. Strategy of empowerment so important to increase engagement so role of nurse managers creating a work environment and improve the quality of services provided to the patient. Keywords: empowerment, quality of nursing work life, nurse, hospital